Mixed Methods Analysis: Traditional Medication,Stigma, and Leper’s Family Support Roles in Level II Leprosy Disability - Irwan Saputra; T.M. Rafsanjani; Said Usman (Institute of Medico-legal Publications Pvt Ltd, 2021)
People with a level II leprosy disability have limited functions in society. In Nagan Raya District, there is a 41% leprosy endemic area with a 5% level II disability rate. The goal of this research was to prove the relationships of traditional medication, stigma, and leper’s family support to level II leprosy disability. This research used mixedmethodsand a case-control design with 84 respondents42 case respondents (level II leprosy disability) and 42 control respondents (level 0 leprosy disability)chosen by consecutive sampling under some inclusion and exclusion criteria. Data collection used the in-depth interview method. This study used bivariate data analysis with the chi-square test and multivariate data analysis with the logistic regression test and the Miles and Huberman’s model. The results of the chi-square analysis indicated that traditional medication had p value=0.014 (OR: 2.3; 95% CI: 0.2–7.7), stigma p=0.04 (OR:3.6;95% CI: 1.5–8.9), and family’s support p=0.192 (OR:2.0; 95% CI: 0.7–5.8). The results of the logistic regression analysis showed that stigma was a risk factor for leprosy level II disability with p value=0.006, (OR=4.9; 95% CI: 1.6–15.1) and probability of 99.96%. Based on the interview results, lepers were feeling uncomfortable with the society’s not acceptingthem in a good way. This was especially the case with khanduri(feast) when it came down to food in that the society assumed lepers would transmit the infectious, disgusting disease. The Nagan Raya District Health Office is expected to encourage the societyto accept lepers and provide information regarding the process of leprosy transmission so as to appease the community’s fearand to prevent further disability.